Bead-making lab : 52 explorations for crafting beads from polymer clay, plastic, paper, stone, wood, fiber, and wire /: 52 explorations for crafting beads from polymer clay, plastic, paper, stone, wood, fiber, and wire. (2016) - Powers, Heather
No abstract available